2011
DOI: 10.1074/jbc.m111.299164
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Transmembrane Segment TM3 in the Xanthine Permease XanQ of Escherichia coli

Abstract: Background:The xanthine permease XanQ is a prototype of nucleobase:proton symporters of the ubiquitous family NCS2. Results: Site-directed replacements of Asn-93 and Phe-94 in the third transmembrane segment of XanQ distort the specificity for substrate. Conclusion: Asn-93 interacts with xanthine-coordinating residues in the binding pocket. Significance: Dissecting specificity determinants in family NCS2 is crucial for understanding evolution of purine uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
45
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(50 citation statements)
references
References 23 publications
4
45
0
1
Order By: Relevance
“…As a result, homology modeling has been used as a reasonable alternative in cases where no x-ray structure is available (23,48,59,61,(67)(68)(69)(70)(71)(72)(73). Using this approach, combined with induced fit docking and a detailed characterization of the specificity profile, we identified 9 residues that are important for PrnB function, Gly 56 Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, homology modeling has been used as a reasonable alternative in cases where no x-ray structure is available (23,48,59,61,(67)(68)(69)(70)(71)(72)(73). Using this approach, combined with induced fit docking and a detailed characterization of the specificity profile, we identified 9 residues that are important for PrnB function, Gly 56 Table 5).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the side chain of Thr-100 is linked with the transporter ability to differentiate between uric acid (8-oxyxanthine) and xanthine. A similar role has been proposed for the corresponding amino acid in permease XanQ (Asn-93) because replacement of Asn-93 with Ala or Ser converts the xanthine-selective XanQ to dual-selectivity variants (7,10); in the case of XanQ, however, the dual-selectivity variants transport the non-wild-type substrate (uric acid) with very low capacity (10). The selectivity-related role of Thr-100/Asn-93 appears to be unique because no other single-replacement mutant of either XanQ (6 -10) or YgfU (this study) has been shown to convert the native transporter to a dual-selectivity one.…”
Section: Discussionmentioning
confidence: 99%
“…2). Most importantly, as well, critical roles have been described for the corresponding residues of other known NAT homologs (1,(7)(8)(9)(10)(11)(12)(13)43), as addressed in more detail below.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations